Membranes of MnO Beading in Carbon Nanofibers as Flexible Anodes for High-Performance Lithium-Ion Batteries - Zhao, Xin (Sci Rep, 2015)
Freestanding yet flexible membranes of MnO/carbon nanofibers are successfully fabricated through incorporating MnO(2) nanowires into polymer solution by a facile electrospinning technique. During the stabilization and carbonization processes of the as-spun membranes, MnO(2) nanowires are transformed to MnO nanoparticles coincided with a conversion of the polymer from an amorphous state to a graphitic structure of carbon nanofibers. The hybrids consist of isolated MnO nanoparticles beading in the porous carbon and demonstrate superior performance when being used as a binder-free anode for lithium-ion batteries. With an optimized amount of MnO (34.6 wt%), the anode exhibits a reversible capacity of as high as 987.3 mAh g(−1) after 150 discharge/charge cycles at 0.1 A g(−1), a good rate capability (406.1 mAh g(−1) at 3  A g(−1)) and an excellent cycling performance (655 mAh g(−1) over 280 cycles at 0.5 A g(−1)). Furthermore, the hybrid anode maintains a good electrochemical performance at bending state as a flexible electrode.